Circ_0006646 Promotes the Progression of Osteoarthritis via Upregulating CDH11 Expression in an IGF2BP2‐Dependent Manner - Hua, Ming‐Yu; Wang, Guo‐Liang; Duan, Wen‐Hao; Tang, Xiao‐Heng (The Kaohsiung journal of medical sciences, 2025)
ABSTRACT Osteoarthritis (OA) is a common degenerative osteoarthropathy with an unclear pathogenesis. Circular RNA (circRNA) has been reported to be associated with OA progression. This study aims to explore the role and potential mechanism of hsa_circ_0006646 in OA. Interleukin‐1β (IL‐1β)‐induced human chondrocytes were used as the cell model of OA. RT‐qPCR and western blotting were used to detect the expression of circ_0006646, IGF2BP2, and cadherin 11 (CDH11). Cell counting kit‐8 assay, 5‐ethynyl‐2′‐deoxyuridine assay, and flow cytometry were performed to assess chondrocyte cell proliferation and apoptosis, respectively. Western blot assay was performed to determine the levels of proliferation‐related proteins, apoptosis‐related proteins, and extracellular matrix (ECM) proteins. RNA immunoprecipitation (RIP) assay was performed to verify the interaction between IGF2BP2 and circ_0006646 or CDH11. In OA patients and IL‐1β‐stimulated chondrocytes, circ_0006646 and CDH11 were upregulated. IL‐1β suppressed proliferation and induced apoptosis, inflammation, and ECM degradation in chondrocytes, and circ_0006646 knockdown protected chondrocytes from IL‐1β‐induced damage. IGF2BP2 was proved to interact with both circ_0006646 and CDH11. The overexpression of IGF2BP2 or CDH11 enhanced IL‐1β‐induced apoptosis, inflammation, and ECM degradation in chondrocytes. Moreover, circ_0006646 absence‐mediated effects in IL‐1β‐treated chondrocytes could be largely overturned by the overexpression of IGF2BP2 or CDH11. In conclusion, circ_0006646 knockdown protected chondrocytes from IL‐1β‐induced injury by regulating CDH11 in an IGF2BP2‐dependent manner, suggesting a novel potential target for OA treatment.